A comparative analysis of molecular genotypes of Mycobacterium tuberculosis isolates from HIV-positive and HIV-negative patients - Singh, Jitendra; Singh, Niti; Suresh, Gayatri; Srivastava, Rahul; Aggarwal, Upasna; Behera, Digamber; Munisamy, Murali; Malhotra, Anvita Gupta; Singh, Sarman (Frontiers in Cellular and Infection Microbiology, 2022)
Setting: Tuberculosis Research Laboratory, Division of Clinical Microbiology and Molecular Medicine, Department of Laboratory Medicine, All India Institute of Medical Sciences, and National Institute of Tuberculosis and Respiratory Diseases (NITRD), both situated at New Delhi. Objectives: We aimed to identify the distribution of various genotypes of M. tuberculosis among HIV-positive and HIV-negative patients suspected with Tuberculosis and seen at the National Institute of Tuberculosis and Respiratory Diseases, New Delhi, which is a tertiary care dedicated TB hospital. Patients and Methods: Genotyping by Spoligotyping and 24 loci MIRU-VNTR was performed and analyzed using SITVITWEB and MIRU-VNTRplus. Drug susceptibility pattern were also analyzed. Results: A total of 503 subjects who were PTB/EPTB suspected were recruited and 287 were culture positive. Among them, 276 had growth of Mycobacterium tuberculosis (MTB) and in 11 patients non-tuberculous mycobacteria (NTM) were grown. The isolation rate of NTM was predominantly from HIV-positive [10 of 130 (7.6%)] patients. Of the total isolates of MTB, 156 (56.5%) were from HIV-negative and 120 (43.5%) from HIV-positive patients. All 276 M. tuberculosis isolates were genotyped and tested for drug susceptibility patterns. The CAS genotype was most predominant [153 (55.4%)], followed by Beijing lineage [44 (15.9%)], East African India [25 (9.1%)] and others [54 (19.6%)]. Beijing genotype was significantly more common in HIV-positive patients (22.5%) than in HIV-negative patients (10.9%). In MIRU-VNTR analysis, clustering was found to be more frequent in CAS strains irrespective of HIV status. In HIV positive group, spoligotyping could differentiate various genotypes in 90% of isolates and MIRU-VNTR analysis in 84.2% of isolates. Clustering of various MTB strains was more associated with drug resistance. Conclusion: The Beijing lineage was predominant in HIV-TB coinfected cases, even though Central Asian Strain (CAS) was overall more predominant in the region.